Performance of modern syringe infusion pump assemblies at low infusion rates in the perioperative setting. (February 2020) - Baeckert, Martina; Batliner, Martin; Grass, Beate; Buehler, Philipp K.; Daners, Marianne Schmid; Meboldt, Mirko; Weiss, Markus
Abstract: Background: Syringe infusion pumps are used for the precise continuous administration of intravenous drugs. Their compliance and mechanical deficiencies have been found to cause considerable start-up delays, flow irregularities during vertical displacement, as well extensive delays of occlusion alarms at low infusion rates. The aim of this study was to evaluate the performance of several modern syringe infusion pumps at low infusion rates and the impact on drug concentration. Methods: Seven currently marketed syringe infusion pump assemblies were assessed in an in vitro study during start-up, vertical displacement manoeuvres, and infusion line occlusion at a set flow rate of 1 ml h −1 . The measured data were used as input for a pharmacokinetic simulation modelling plasma concentration during a standard neonatal continuous epinephrine infusion. Results: The mean time from starting the infusion pump to steady-state flow varied from 89 to 1622 s. The zero-drug delivery time after lowering the pump ranged from 145 to 335 s. In all assemblies tested, occlusion alarm delays and measured flow irregularities during vertical displacement manoeuvres resulted in relevant deviations in plasma epinephrine concentration (>25%) as calculated by the pharmacokinetic simulation model. Conclusion: Problems with the performance of syringe infusion pump assemblies can have considerable impact on plasma drug concentration when highly concentrated short-acting cardiovascular drugs are administered at low flow rates. The problems, which affected all assemblies tested, are mainly related to the functional principle of syringe infusion pumps and will only partially be solved by incremental improvements of existing equipment.